Monitoring of maize root growth on N, P, and K fertilization using rhizotron - Fajrin Pramana Putra; Roni Ismoyojati (Jurnal Ilmiah Pertanian, 2021)
Maize roots will show varying growth responses to the type of fertilizer given. The objective of this study was to determine the effect of N, P, and K fertilizers on the growth of maize roots and the function of the relationship between root dry weight and shoot dry weight of maize under rizhotron. The research was conducted in April - June 2019 at the screen house and Plant Laboratory, Politeknik Lamandau in Lamandau Regency. The research was conducted in rizhotron's growth medium which was arranged in a completely randomized design (CRD) with a fertilizer treatment consisting of urea (N = 200 kg ha-1), SP36 (P = 100 kg ha-1), KCl (K = 100 kg ha-1), and control (without fertilizer) with three replications. The results showed that N fertilizer was able to provide better root dry weight growth compared to P and K fertilizer, namely 2.59 g. Root dry weight has a significant effect on plant dry weight gain based on the function of y = 4.10x + 0.06 (R2 = 0.96 **).